The Effect of the Double Loop Problem Solving (DLPS) Learning Model on the Mathematics Learning Outcomes of Class VIII Students of SMP N 2 Tilatang Kamang - Riska Riska; Vivi Ramdhani; M. Imamuddin; Risnawita Risnawita (Darul Yasin Al Sys, 2026)
This study is motivated by the results of analysis and observation of the Daily Mathematics Test in eighth-grade classes at SMP N 2 Tilatang Kamang, which showed low students’ mathematics learning outcomes and teacher-centered instruction. One alternative strategy to address this issue is the implementation of the Double Loop Problem Solving (DLPS) learning model. This study aims to examine the effect of the DLPS learning model on the mathematics learning outcomes of eighth-grade students at SMP N 2 Tilatang Kamang. A pre-experimental design with a Static Group Comparison Design was employed. The population consisted of all eighth-grade students at SMP N 2 Tilatang Kamang, comprising four classes with a total of 101 students. Sampling was conducted randomly after normality, homogeneity, and mean equivalence tests were performed on the population data. Class VIII.2 was assigned as the experimental group, while Class VIII.1 served as the control group. The research instrument was a posttest designed to measure students’ mathematics learning outcomes. Data were analyzed using a t-test. The findings show that the t-count value was 3.696, while the t-table value was 1.67. Since the t-count exceeded the t-table, H₀ was rejected and H₁ was accepted. The SPSS analysis also produced a p-value of 0.01, indicating a statistically significant difference in mathematics learning outcomes between the experimental and control groups. These results demonstrate that the DLPS learning model has a significant effect on students’ mathematics learning outcomes. The study contributes to mathematics education by providing empirical evidence that problem-solving-oriented learning can improve students’ achievement and reduce reliance on teacher-centered instruction.